COMPARATIVE PEDAGOGICAL ANALYSIS OF GIRLS’ UPBRINGING IN EASTERN AND WESTERN CULTURES (Web of Teachers: Inderscience Research, 2026)
This study investigates the upbringing of girls in Eastern and Western cultural contexts through a comparative pedagogical perspective. By examining historical, social, and educational practices, the research identifies how cultural values influence moral education, social development, and gender role formation. The methodology combines a comprehensive literature review with historical document analysis and qualitative comparative evaluation. Findings indicate that Eastern cultures often prioritize family-centered values, moral discipline, and collective responsibility, whereas Western cultures emphasize personal autonomy, self-expression, and rights-based education. The study highlights the importance of culturally responsive pedagogy in fostering balanced intellectual, social, and ethical development in girls, offering recommendations for integrating best practices across diverse cultural settings.